Psychological distress and its relation to coping strategies among firefighters and civil defence force involved in the massive flood disaster in Kelantan - Fazil, Ahmad (2017)
There were many studies that reported the psychological impact of flood disaster to victims, however data on rescue workers, especially firefighters and civil defence force in Malaysia are scarce. The rescue workers are at an increased risk of developing a psychological distress after being exposed to traumatic events during the disaster.This study aimed at determining the prevalence of Post-Traumatic Stress Disorder (PTSD), Depression, Anxiety and Stress and its associated factors among firefighters and civil defence force rescue workers six months after the flood disaster in Kelantan. A cross sectional study among 160 firefighters and civil defence force rescue workers were conducted in July 2015, using the Malay translated and validated Impact Event Scale -Revised (IES-R) and DASS 21 to detect PTSD, Depression, Anxiety and Stress and Brief-COPEMalay version to evaluate the types of coping strategies used. Data were analyzed using multiple logistic regressions. The study found that the prevalence of PTSD among firefighters and civil defence force rescue workers in Kelantan was 20.6%. In the final model, four variables remained significant which were age [ORadj 0.94 (95%CI 0.89 - 0.99)], denial coping [ORadj 1.89 (95%CI 1.31 - 2.71)], focus on and venting of emotion coping [ORadj 1.49 (95%CI 1.01 - 2.22)] and planning coping [ORadj 3.34 (95%CI 2.03 - 5.48)]. The prevalence of depression was 19.4%. The final model showed that three variables remained significant which were pre-disaster training [ORadj 0.26 (95% CI 0.07, 0.92)], planning coping strategies [ORadj 3.72 (95% CI 2.24, 6.17)] and self-blame coping strategies [ORadj 1.75 (95% CI 1.21,2.52)]. The prevalence of anxiety was 29.4%. The final model showed that two variables remained significant which were planning coping strategies [ORadj 8.64 (95% CI 4.39,17.00)] and self-blame coping strategies [ORadj 1.63 (95% CI 1.10, 2:42)]. The prevalence of stress was 13.1%. The final model showed that two variables remained significant which were planning coping strategies [ORadj 8.04 (95% CI 3.34,19.32)] and humour coping strategies [ORadj 1.78 (95% CI 1.15, 2:76)]. In conclusion, the prevalence of PTSD, Depression, Anxiety and Stress among firefighters and civil defence force rescue workers were significantly high and associated with the use of less useful or emotional focused coping strategies including denial, focus on and venting of emotion, planning, self-blame and humour whereby protective effect to psychological distress among them were an increasing of age and pre-disaster training. Therefore, there is a need to incorporate psychological component in the pre-disaster training for rescue workers in Malaysia.